Upaya Meningkatkan Hasil Belajar IPS Dalam Materi Lingkungan Melalui Model Pembelajaran Picture And Picture - Hidayati, Nur Rohman (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
According to the results of the evaluation of the level of mastery of the subject matter at the first meeting, it was still low in Social Studies lessons in the material of the natural environment and the built environment, only 6 out of 15 students scored above the KKM (70). The purpose of this learning improvement is to improve learning outcomes in the social studies learning process with environmental material. The research method uses two cycles with the picture and picture learning model. The repairs were carried out in class III at SDN 01 Jatiroyo, Jatipuro District, Karanganyar Regency, with a total of 15 students consisting of 7 male students and 8 female students. The results of student evaluations started from the pre-cycle, cycle 1, and cycle 2. It was proven that the evaluation scores in the pre-cycle were 6 out of 15 students who took the KKM, Cycle 1 to 9 students. In cycle 2 it increased to 15 students. The conclusion of improving learning can improve student learning outcomes in social studies lessons by applying learning models.